2016
DOI: 10.1097/bcr.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Subcutaneous White Adipose Tissue After Severe Burn Injury

Abstract: Introduction Severe burn injury produces a plethora of metabolic abnormalities which contribute to the prolonged morbidity of burn survivors. We have recently demonstrated trans-differentiation of white adipose tissue following burn trauma, towards a more thermogenic phenotype. However, the impact of burn injury on subcutaneous WAT (sWAT) morphology in humans is unknown. Here, we studied the effect of severe burn injury on the architecture of sWAT. Methods sWAT was collected from eleven severely burned child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
(25 reference statements)
0
20
0
1
Order By: Relevance
“…Cardiac fibrosis is also noted. Of note, patients with burn injury also display a higher collagen content in their adipose tissue, arguing for a role of adipose tissue remodeling in burn injuries, too (Saraf et al, 2016 There certainly is evidence for increased fibrosis in cachectic adipose tissue, both in mice and men (Mracek et al, 2011;Batista et al, 2016;Luo et al, 2016).…”
Section: Fibrosis and Adipose Tissue Stiffness In Wastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac fibrosis is also noted. Of note, patients with burn injury also display a higher collagen content in their adipose tissue, arguing for a role of adipose tissue remodeling in burn injuries, too (Saraf et al, 2016 There certainly is evidence for increased fibrosis in cachectic adipose tissue, both in mice and men (Mracek et al, 2011;Batista et al, 2016;Luo et al, 2016).…”
Section: Fibrosis and Adipose Tissue Stiffness In Wastingmentioning
confidence: 99%
“…However, whether this is cause or consequence of the tissue wasting in cachexia remains to be investigated. Of note, patients with burn injury also display a higher collagen content in their adipose tissue, arguing for a role of adipose tissue remodeling in burn injuries, too (Saraf et al, 2016).…”
Section: Fibrosis and Adipose Tissue Stiffness In Wastingmentioning
confidence: 99%
“…Moreover tissue cytokines IL-6, IL-8, IL-13, IL-1α, IL-1β, MCP-1, and TNF-α were all significantly greater in the sWAT of burned vs healthy subjects, providing an ostensible link between morphological/functional changes in sWAT and tissue inflammation [19]. Arachidonic acid is elevated in sWAT, and correlate strongly with macrophage presence in obese women with type 2 diabetes mellitus [20].…”
Section: Introductionmentioning
confidence: 93%
“…The authors suggested these changes as potential contributors of disorders such as lipolysis, fibrosis and hypermetabolism in burn, mediated by inflammation. 16 It should be noted that subcutaneous WAT samples were obtained from different anatomical regions in this study. In addition, WAT interleukin (IL)-13 levels were higher in the children with burns compared with the healthy group.…”
Section: Morphological and Metabolic Changes Of Adipose Tissue In Cmentioning
confidence: 99%